Teknik Pengisian Ulang Baterai Alkaline Nonrecharable Bekas Untuk Memperpanjang Umur Pemakaian - I Nyoman Wahyu Satiawan; Supriono Supriono; Ida Bagus Fery Citarsa; I Made Budi Suksmadana; Warindi Warindi (LPPM Universitas Mataram, 2021)
Alkaline battery is one type of battery that is designed for single use. As a result, there is a lot of waste or alkaline battery waste. To reduce the impact of alkaline battery waste, it is deemed necessary to conserve batteries, namely by extending their service life, thereby delaying the battery to become waste. The easy way is to recharge the battery so that it can be used again. Although alkaline batteries are disposable batteries, from the characteristics of the electrochemical reactions it can be seen that the chemical reactions can be reversed so that there is a possibility that the batteries can be recharged. Some of the limitations in recharging include the condition of the battery, recharging strategy, the limit on the number of charging cycles and the capacity of the battery when it is recharged. This paper discusses the procedure for conserving used alkaline batteries to increase the use time and at the same time reduce the negative impact of battery waste on the environment. The stages of the battery charging experiment are: 1) detecting the quality of used alkaline batteries, 2) determining the proper way of recharging and 3) estimating the number of safe recharge cycles before being recycled. The experimental results show that: 1) the detection of rechargeable batteries can be carried out by the short initial charge method and checking whether there is an increase in battery capacity, 2) the combined method of constant voltage and constant current is the fastest and safest way to recharge alkaline batteries, 3) the average alkaline battery can be recharged up to 8 times.